A Bright IDEA. Issue 4 (6th April 2020) - Jackson, Christopher; Gresham, David
Abstract : Transcription factors (TFs) control the rate of mRNA production. Technological advances have made the task of measuring mRNA levels for all genes straightforward, but identifying causal relationships between TFs and their target genes remains an unsolved problem in biology. In their recent study, McIsaac and colleagues (Hackett et al, 2020) apply a method for inducing the overexpression of a TF and studying the dynamics with which all transcripts respond. Using time series analysis, they are able to resolve direct effects of TFs from secondary effects. This new experimental and analytical approach provides an efficient means of defining gene regulatory relationships for all TFs. Abstract : Identifying causal regulatory relationships between transcription factors(TFs) and their target genes remains an unsolved problem. In their recent study, McIsaac and colleagues develop a method to resolve direct effects of TFs from secondary effects.